Evaluation of neutrophil-to-lymphocyte ratio and platelet-to-lymphocyte ratio in pregnant women with systemic lupus erythematosus. (4th July 2022) - Ekici, Huseyin; Imamoglu, Metehan; Okmen, Firat; Gencosman, Gizem; Ak, Gunes; Ergenoglu, Mete
Abstract: Systemic lupus erythematosus (SLE) is associated with a higher risk of complications in pregnancy. Neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) have been evaluated in numerous inflammatory diseases. We evaluated the possible role of these markers in SLE pregnancies. Forty-six pregnant patients with an already established diagnosis of SLE were included in the study. Complete blood counts were obtained upon admission for delivery. Seven patients were diagnosed with a flare and managed with multiple medications, whereas rest of the patients were not on any treatment or managed with monotherapy. NLR and PLR values were also evaluated between two groups and no statistically significant difference was found ( p =.44 and p =.80, respectively). This study is the first to evaluate the possible role of NLR and PLR in pregnant SLE patients in the literature. Further studies are warranted for an elaborate evaluation of NLR and PLR in lupus pregnancies. Impact Statement: What is already known on this subject? Pregnancy in the setting of SLE is associated with a higher risk of complications. Active disease increases the risk of adverse outcomes further. What the results of this study add? This study is the first to evaluate NLR and PLR in pregnancies complicated by SLE. No significant association between the course of the disease in pregnancy and NLR/PLR was documented. What the implications are of these findings for clinical practice and/or further research? Further studies on the markers to predict prognosis of SLE in pregnancy are required to improve the maternal and neonatal outcomes in this exclusive group of high-risk patients.